2019
DOI: 10.3389/fmicb.2019.02825
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus Utilizes Cholesterol Transporter NIEMANN–Pick C1 for Host Cell Entry

Abstract: The dual roles of baculovirus for the control of natural insect populations as an insecticide, and as a tool for foreign gene expression and delivery, have called for a comprehensive understanding of the molecular mechanisms governing viral infection. Here, we demonstrate that the Bombyx mori Niemann-Pick C1 (BmNPC1) is essential for baculovirus infection in insect cells. Both pretreatment of B. mori embryonic cells (BmE) with NPC1 antagonists (imipramine or U18666A) and down-regulation of NPC1 expression resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…The cholesterol transporter BmNPC1 interacts with GP64. Its deficiency inhibits viral penetration rather than viral binding to BmE cells ( 29 ). In contrast, BmNPV BV uses clathrin- and dynamin-dependent endocytosis pathways to penetrate BmN cells.…”
Section: Baculovirus Host Invasion Mechanismmentioning
confidence: 99%
“…The cholesterol transporter BmNPC1 interacts with GP64. Its deficiency inhibits viral penetration rather than viral binding to BmE cells ( 29 ). In contrast, BmNPV BV uses clathrin- and dynamin-dependent endocytosis pathways to penetrate BmN cells.…”
Section: Baculovirus Host Invasion Mechanismmentioning
confidence: 99%
“…We performed RNAi to the chloride intracellular channel gene and found that the copy numbers of the virus were not significantly changed. As previous report that the NPC-1 gene was an essential host factor in BmNPV infection [ 17 ], therefore the NPC-1 was selected as a candidate gene for further research.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that it was also severe as a virus intracellular receptor for filovirus entry, such as Ebola virus and Marburg virus; the mutation of domain C would result in complete resistance to virus infection [ 13 , 14 , 15 , 16 ]. A recent study showed that NPC-1 was also an essential host factor for baculovirus infection in insect cells, it may interact with the GP64 of BmNPV to facilitate the virus’ entry [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coincidentally, the same phenotype was observed in the viruses with BmNPV GP64 fusion loops that had been mutated in our previous study (Bifang Hao, Lin Liu, Na Liu, Wenbin Nan, Fengxiu Fan, Jinshan Huang, unpublished data). We found that macropinocytosis was employed by BmNPV to invade host cells ( 1 , 22 ), and virions were transported into endolysosomes, in which GP64 interacted with the Niemann-Pick type C1 (NPC1) transporter ( 5 ). NPC1 is a cholesterol transporter that interacts with Ebola virus glycoprotein priming by cathepsin L in the endolysosome and mediates virus infection with other host factors ( 23 ); thus, cholesterol, NPC1, GP64, or other viral proteins may cooperate to mediate BmNPV entry.…”
Section: Cholesterol Replenishment Rescued Failed Cell-cell Fusionmentioning
confidence: 99%